The Transforming Outcomes for Patients Through Medical Home Evaluation and reDesign (TOPMED) Cluster Randomized Controlled Trial: Cost and Utilization Results. Issue 2 (10th February 2022) - Colasurdo, Joshua; Pizzimenti, Christie; Singh, Sumeet; Ramsey, Katrina; Ross, Rachel; Sachdeva, Bhavaya; Dorr, David A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Primary Care Medical Home (PCMH) redesign efforts are intended to enhance primary care's ability to improve population health and well-being. PCMH transformation that is focused on "high-value elements" (HVEs) for cost and utilization may improve effectiveness. Objectives: The objective of this study was to determine if a focus on achieving HVEs extracted from successful primary care transformation models would reduce cost and utilization as compared with a focus on achieving PCMH quality improvement goals. Research Design: A stratified, cluster randomized controlled trial with 2 arms. All practices received equal financial incentives, health information technology support, and in-person practice facilitation. Analyses consisted of multivariable modeling, adjusting for the cluster, with difference-in-difference results. Subjects: Eight primary care clinics that were engaged in PCMH reform. Measures: We examined: (1) total claims payments; (2) emergency department (ED) visits; and (3) hospitalizations among patients during baseline and intervention years. Results: In total, 16, 099 patients met the inclusion criteria. Intervention clinics had significantly lower baseline ED visits ( P =0.02) and claims paid ( P =0.01). Difference-in-difference showed a decrease in ED visits greater in control than intervention (ED per 1000 patients: +56; 95% confidence interval: +96, +15) with a trend towards decreased hospitalizations in intervention (−15; 95% confidence interval: −52, +21). Costs were not different. In modeling monthly outcome means, the generalized linear mixed model showed significant differences for hospitalizations during the intervention year ( P =0.03). Discussion: The trial had a trend of decreasing hospitalizations, increased ED visits, and no change in costs in the HVE versus quality improvement arms.